MSMEs Marketing Strategy During the Covid 19 Pandemic To Achieve Competitive Advantage - Joni Hendra; Sudarmiatin; Agus Hermawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
During the COVID-19 pandemic, in general, some small entrepreneurs otherwise known as MSMEs experienced quite difficult conditions, in addition to a decline in people's purchasing power, as well as increasingly fierce business competition, both nationally and internationally. Even so, it cannot be denied that MSMEs have contributed a lot to economic growth in Indonesia, especially in the Probolinggo Region. The purpose of this study is (1) to analyze how small and medium-sized enterprises cope with environmental changes due to the COVID-19 pandemic, (2) to find out the marketing strategies used by Small and Medium Enterprises related to current digital technology support. To achieve this goal, The research uses a case study method or design with a SWOT analysis to assess and help SMEs determine the right marketing strategy and anticipate changes in the business environment. From this research, it was found 4 marketing strategies for MSMEs to increase competition or competitiveness, namely SO MSMEs Strategy to innovate, create product characteristics and utilize digital technology as a promotional and sales medium. W-O Strategy. MSMEs actors are required to always pay close attention to any demand for market share and also consumers who want MSMEs to continue to innovate in product value. The ST strategy, products produced by MSMEs actors should have a distinctive value and provide protection for products by creating their own trademarks. While the W-T strategy, introduces products that are superior outside of product clustering in the region, and has products that are packaged innovatively.